The Lake Mead Intake 3 Water Tunnel and Pumping Station, Las Vegas, Nevada, USA - Michael Feroz; Marcus Jensen; James E. Lindell (Society for Mining, Metallurgy & Exploration, 2007)
The Southern Nevada Water Authority (SNWA) operates two water-intakes in Lake Mead, located 20 miles east of Las Vegas, Nevada. Severe drought has caused decline in lake level by 85 feet since 2000 and future declines are expected. SNWA will construct a third deep-water intake to ensure existing water system capacity. This paper describes expected construction challenges for the new project that consists of: an intake structure and tunnel beneath the lake, pumping station, pipeline to connect existing treatment facility, and interconnecting underground adits. The project will be completed in the year 2012 for total estimated cost of approximately $600 million.